Challenges of Innovative Institutions in the Tourism Sector in Algeria: A Sample Study of Start-ups - Narimane BENABDERRAHMANE,; Soumia AMRAOUI, (Journal of North African Economies, 2025)
This study aims to investigate the challenges faced by innovative institutions in Algeria's tourism sector by examining the most significant obstacles encountered by tourism Start-ups within their ecosystem. Through a sample of emerging tourism start-ups in Algeria, the research aims to delve into various challenges: legal and administrative hurdles, commercial and marketing challenges, and service-related and financial challenges confronting the operations of these startups. The findings elucidate that the foremost administrative and legal challenge facing tourism Startups in Algeria is the absence of integration and collaboration among stakeholders in the ecosystem. Additionally, there is a notable challenge in terms of e-governance. Concerning service-related challenges, grappling with the nature of the financial and tax system, as well as e-payment, stands out as one of the most significant obstacles facing the activities of these institutions. Regarding commercial and marketing challenges, marketing services on the international market pose a substantial hurdle.